Effect of cooking time and temperature on extraction yield and antioxidant properties of Beef Rendang - Ithnin, Nur Huwaidah; Selamat, Jinap; Murugesu, Suganya; Hew, Peir Shinn; Sukor, Rashidah; Karim, Siti Nabilah (Universiti Sains Islam Malaysia, 2023)
Rendang is a popular traditional cuisine in Southeast Asia, particularly Malaysia and Indonesia. Rendang ingredients vary according to different countries and mainly consist of spices, coconut milk, and meat, either chicken or beef. Spices such as coriander, fennel, cumin, ginger, galangal, lemongrass, garlic, and onion used in rendang mostly contributed to its antioxidant properties. However, the beef rendang's antioxidant properties may be lost due to the long cooking period. This study aims to determine the effect of cooking time and temperature on the extraction yield and antioxidant properties of beef. Rendang samples prepared using lean beef and mixed with coconut milk and other spices were collected every hour up to five hours of cooking. The samples were subjected to methanol extraction for total phenolic content (TPC) and 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay using Folin-Ciocalteu and DPPH solution, respectively. The data were analysed by one-way analysis of variance (ANOVA) followed by Tukey's test. Data for extraction yield showed that rendang samples cooked for one and two hours had significantly lesser yield (p<0.05) than those cooked for three to five hours. For TPC analysis, rendang that was cooked for three hours had the highest total phenolic content (8.018 ± 0.911 mg GAE/g) (p<0.05) compared to those that were cooked for one, two, four, and five hours (4.205±0.364, 2.368±0.127, 2.746±0.080, and 1.839±0.110 mg GAE/g). For the DPPH assay, one-hour beef rendang sample had the lowest EC50 (20.278±0.733 µg/ml) (p<0.05) followed by those cooked for two, three, four, and five hours (39.041±1.368, 40.143±4.502, 48.338±2.115, and 58.159±3.060 µg/ml), indicating a low EC50 value which exhibited high antioxidant power. It can be concluded that antioxidant properties were significantly lost due to prolonged heating with increasing cooking time.